Implementation of the Verdict of Constitutional Concerning the Inclusion of Confidentially of Trust in Electronic Identity Card (E-KTP) and Family Card (KK) Column as a Legal Protection to the Constitutional Rights of the Confidentially Trust - Eko Yudhistira, Rosnidar Sembiring , Zulfi Chairi (International Journal of Advanced Science and Technology, 2020)
In 2017 Constitutional Court release the verdict Number: 97/PU-XIV/2016. The verdict grant the demands of the followers of the faith to change the terms of emptying the column of religion for adherents of belief that is not recognized by the State as a religion on the KTP and KK. The verdict is aimed at protecting trustees from discriminatory administrative regulations. The Parmalim community as one of the groups that believe is also certainly feel the impact. 20 out of 30 residents who live in the village of Huta Tinggi, Toba Samosir, North Sumatera, Indonesia, the center of Parmalim's trust activities, stated that they still often experience stigma and bad behavior from the public when the community knows they are supporters of the trust. The state should protect their rights in adhering to trust as one of the constitutional rights but whether the Constitutional Court's ruling has fulfilled their constitutional rights. This study aims to see how the implementation of the Constitutional Court's decision and its impact on the social life of the Parmalim community in the village of Huta Tinggi, District Lagu Boti, Toba Samosir Regency. Furthermore, this study will compare how the conditions experienced and faced by the Parmalim community before and after the Constitutional Court Decision. Not only in obtaining identity cards and family cards but also in registering marriages for Parmalim followers.